High-transmittance PVC (polyvinyl chloride) film and preparation method thereof
By using raw materials such as modified nanocellulose and modified filler agents in the PVC film, combined with silane coupling agent and epoxy soybean oil, the problems of poor light transmission performance and unstable mechanical properties of existing PVC films are solved, and the preparation of high-transmittance PVC films is achieved, with excellent light transmittance and mechanical properties, and the stability of temperature and ultraviolet weather resistance is significantly improved.
Patent Information
- Application Number
- CN202510268304.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-07
AI Technical Summary
The existing PVC films have poor light transmission performance, unstable mechanical properties, and insufficient stability in temperature and ultraviolet weather resistance, which limits the efficiency of the product.
PVC resin, modified nanocellulose, modified filler agent, silane coupling agent, epoxy soybean oil, heat stabilizer and lubricant are used to harmonize each other. Through the combination of modified nanocellulose and modified filler agent, the light transmittance and mechanical properties of the system are enhanced.
It significantly improves the light transmittance and mechanical properties of the PVC film, achieves a coordinated balance between light transmittance and mechanical properties, and at the same time improves the product's temperature and ultraviolet weather resistance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of PVC films, and in particular to a high-light-transmittance PVC film and a preparation method thereof. Background Art
[0002] The natural color of polyvinyl chloride is slightly yellow and translucent, with gloss. Its transparency is better than that of polyethylene and polypropylene, but worse than that of polystyrene. Depending on the amount of additives used, it is divided into soft and hard polyvinyl chloride. Soft products are soft and tough, and feel sticky. The hardness of hard products is higher than that of low-density polyethylene, but lower than that of polypropylene, and whitening will occur at the inflection points.
[0003] The existing PVC film has poor light transmittance. In order to improve the light transmittance of the product, it is easy to cause poor mechanical properties of the product. The coordinated and balanced improvement of the two is the technical difficulty of the present invention. At the same time, the product has poor temperature resistance and UV weather resistance, which limits the use efficiency of the product. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a high light-transmittance PVC film and a preparation method thereof to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a high light-transmittance PVC film, comprising the following raw materials in parts by weight: 50-55 parts of PVC resin, 7-11 parts of modified nanocellulose, 6-8 parts of modified filler, 5-8 parts of silane coupling agent, 4-6 parts of epoxidized soybean oil, 2-3 parts of heat stabilizer, and 2-3 parts of lubricant.
[0006] Preferably, the following raw materials are included in parts by weight: 52.5 parts of PVC resin, 9 parts of modified nanocellulose, 7 parts of modified filler, 6.5 parts of silane coupling agent, 5 parts of epoxidized soybean oil, 2.5 parts of heat stabilizer, and 2.5 parts of lubricant.
[0007] Preferably, the silane coupling agent is silane coupling agent KH560; the heat stabilizer is barium zinc heat stabilizer; and the lubricant is sodium stearate.
[0008] Preferably, the preparation method of the modified nanocellulose is: S01: Preparation of modified solution: S011: immerse nano zinc oxide and hydroxyapatite in yttrium nitrate solution and stir evenly, then filter and dry, and then heat calcine at 175-185°C for 1 hour. After calcination, cool naturally to room temperature to obtain nano zinc oxide agent; S012: Add 5-8% of alginate to a 4% chitosan solution, and then add 8% sodium citrate solution which is 2-3 times the total mass of the chitosan solution, and stir evenly to obtain a modified sodium citrate solution; S013: Add 4 to 7 parts of nano zinc oxide and 1 to 3 parts of silane coupling agent KH550 to 5 to 8 parts of modified sodium citrate solution by weight, stir well, and obtain a modified solution; S02: adding nanocellulose to a sufficient amount of modification liquid for ultrasonic modification treatment, and after the modification is completed, filtering and drying are performed to obtain modified nanocellulose.
[0009] Preferably, the mass ratio of the nano zinc oxide, hydroxyapatite and yttrium nitrate solution is (3-4):2:(5-7); wherein the mass fraction of the yttrium nitrate solution is 2-5%.
[0010] Preferably, the ultrasonic modification treatment time is 35-45 min, the ultrasonic power is 400-450 W; and the nanocellulose is lignin nanocellulose.
[0011] Preferably, the preparation method of the modified filler is: S01: Prepare a sodium silicate solution with a mass fraction of 4-7%, then add 1-3 parts of stearic acid, 1-2 parts of sodium dodecyl sulfate and 2-3 parts of nano-alumina agent to 5-8 parts of the sodium silicate solution with a mass fraction of 4-7%, and stir evenly to obtain a modified sodium silicate solution; S02: Preheat nano titanium dioxide at 60°C for 1 hour to obtain preheated nano titanium dioxide; mix the preheated nano titanium dioxide and modified sodium silicate solution in a weight ratio of 2:5, and ball mill them at a ball milling speed of 1000r / min for 2 hours. After the ball milling is completed, filter and dry to obtain a modified filler.
[0012] Preferably, the preparation method of the nano-alumina agent is: stirring the nano-alumina, dopamine hydrochloride solution and lanthanum oxide according to a weight ratio of 3: (5-7): 1, filtering and drying after the stirring is completed to obtain the nano-alumina agent; The mass fraction of the dopamine hydrochloride solution is 3-6%; the stirring speed of the stirring treatment is 450-500 r / min, the stirring is for 1 hour, and the stirring temperature is 60-65°C.
[0013] The present invention also provides a method for preparing a high light-transmittance PVC film, comprising the following steps: The raw materials are weighed according to weight parts, and the raw materials are mixed uniformly to obtain a blend; the blend is melted and extruded in an extruder, and then blown, extruded into a film through a herringbone plate and a traction guide roller, and finally cooled and rolled to obtain a high-light-transmittance PVC film.
[0014] Preferably, the melt extrusion in the extruder adopts a twin-screw extruder, with a first-stage temperature of 180°C, a second-stage temperature of 200°C, a third-stage temperature of 210°C, a screw speed of 50 r / min, and an aspect ratio of 40:1.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The high-light-transmittance PVC film of the present invention adopts PVC resin, silane coupling agent, epoxy soybean oil, heat stabilizer and lubricant to be mutually harmonized, and further reinforced and adjusted by adding modified nanocellulose and modified filler, so that the light transmittance and mechanical properties of the product are improved in a coordinated and balanced manner, and the stability of the product in terms of heat resistance and ultraviolet weather resistance is remarkable; the modified nanocellulose adopts nanocellulose to be treated with the specific modified liquid of the present invention, and the modified liquid adopts nano zinc oxide agent, silane coupling agent KH550 and modified sodium citrate solution to be mutually adjusted and optimized, and the nano zinc oxide agent is treated by immersing nano zinc oxide and hydroxyapatite in yttrium nitrate solution, and then calcined and improved, and the light transmittance of the system is enhanced through the coordination between the raw materials, and at the same time, the modified sodium citrate solution adopts chitosan solution, alginate and other raw materials The interfacial properties between the raw materials of the system are further enhanced by the mutual matching and assistance between the nanocellulose and the modified liquid, which are reinforced into the system to enhance the coordination of the system performance and the stability of the performance; the modified filler is preheated with nano titanium dioxide, and then blended with stearic acid, sodium dodecyl sulfate, nano alumina and sodium silicate solution, and the raw materials in the modified sodium silicate solution are mutually matched and assisted to enhance the blending of nano titanium dioxide and nano alumina, thereby further improving the product performance; the nano alumina agent is blended and coordinated with nano alumina, dopamine hydrochloride solution and lanthanum oxide to further enhance the mutual matching and coordination effect of the nano alumina in the system, thereby enhancing the coordination effect of the modified filler and modified nano cellulose, and further improving the performance of the product. DETAILED DESCRIPTION
[0016] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] A high light-transmittance PVC film of this embodiment includes the following raw materials in parts by weight: 50-55 parts of PVC resin, 7-11 parts of modified nanocellulose, 6-8 parts of modified filler, 5-8 parts of silane coupling agent, 4-6 parts of epoxidized soybean oil, 2-3 parts of heat stabilizer, and 2-3 parts of lubricant.
[0018] The silane coupling agent of this embodiment is silane coupling agent KH560; the heat stabilizer is barium zinc heat stabilizer; and the lubricant is sodium stearate.
[0019] The preparation method of the modified nanocellulose of this embodiment is: S01: Preparation of modified solution: S011: immerse nano zinc oxide and hydroxyapatite in yttrium nitrate solution and stir evenly, then filter and dry, and then heat calcine at 175-185°C for 1 hour. After calcination, cool naturally to room temperature to obtain nano zinc oxide agent; S012: Add 5-8% of alginate to a 4% chitosan solution, and then add 8% sodium citrate solution which is 2-3 times the total mass of the chitosan solution, and stir evenly to obtain a modified sodium citrate solution; S013: Add 4 to 7 parts of nano zinc oxide and 1 to 3 parts of silane coupling agent KH550 to 5 to 8 parts of modified sodium citrate solution by weight, stir well, and obtain a modified solution; S02: adding nanocellulose to a sufficient amount of modification liquid for ultrasonic modification treatment, and after the modification is completed, filtering and drying are performed to obtain modified nanocellulose.
[0020] The mass ratio of nano zinc oxide, hydroxyapatite and yttrium nitrate solution in this embodiment is (3-4):2:(5-7); wherein the mass fraction of yttrium nitrate solution is 2-5%.
[0021] The ultrasonic modification treatment time of this embodiment is 35-45 minutes, and the ultrasonic power is 400-450W; the nanocellulose is lignin nanocellulose.
[0022] The preparation method of the modified filler of this embodiment is: S01: Prepare a sodium silicate solution with a mass fraction of 4-7%, then add 1-3 parts of stearic acid, 1-2 parts of sodium dodecyl sulfate and 2-3 parts of nano-alumina agent to 5-8 parts of the sodium silicate solution with a mass fraction of 4-7%, and stir evenly to obtain a modified sodium silicate solution; S02: Preheat nano titanium dioxide at 60°C for 1 hour to obtain preheated nano titanium dioxide; mix the preheated nano titanium dioxide and modified sodium silicate solution in a weight ratio of 2:5, and ball mill them at a ball milling speed of 1000r / min for 2 hours. After the ball milling is completed, filter and dry to obtain a modified filler.
[0023] The preparation method of the nano-alumina agent of this embodiment is as follows: nano-alumina, dopamine hydrochloride solution and lanthanum oxide are stirred in a weight ratio of 3: (5-7): 1, and after stirring, the stirring is completed, the nano-alumina agent is filtered and dried to obtain the nano-alumina agent; The mass fraction of the dopamine hydrochloride solution is 3-6%; the stirring speed of the stirring treatment is 450-500 r / min, the stirring is for 1 hour, and the stirring temperature is 60-65°C.
[0024] A method for preparing a high light-transmittance PVC film of this embodiment comprises the following steps: The raw materials are weighed according to weight parts, and the raw materials are mixed uniformly to obtain a blend; the blend is melt-extruded in an extruder, and then blow-molded, extruded into a film through a herringbone plate and a traction guide roller, and finally cooled and rolled to obtain a high-light-transmittance PVC film.
[0025] The melt extrusion in the extruder of this embodiment adopts a twin-screw extruder, the temperature of the first section is 180°C, the temperature of the second section is 200°C, the temperature of the third section is 210°C, the screw speed is 50r / min, and the aspect ratio is 40:1.
[0026] Embodiment 1: A high light transmittance PVC film, comprising the following raw materials in parts by weight: 50 parts of PVC resin, 7 parts of modified nanocellulose, 6 parts of modified filler, 5 parts of silane coupling agent, 4 parts of epoxidized soybean oil, 2 parts of heat stabilizer, and 2 parts of lubricant.
[0027] The silane coupling agent of this embodiment is silane coupling agent KH560; the heat stabilizer is barium zinc heat stabilizer; and the lubricant is sodium stearate.
[0028] The preparation method of the modified nanocellulose of this embodiment is: S01: Preparation of modified solution: S011: immerse nano zinc oxide and hydroxyapatite in yttrium nitrate solution and stir evenly, then filter and dry, and then heat calcine at 175°C for 1 hour. After calcination, cool naturally to room temperature to obtain nano zinc oxide agent; S012: adding 5% of alginate to a 4% chitosan solution, and then adding 8% sodium citrate solution twice the total mass of the chitosan solution, and stirring evenly to obtain a modified sodium citrate solution; S013: Add 4 parts of nano zinc oxide agent and 1 part of silane coupling agent KH550 to 5 parts of modified sodium citrate solution by weight, stir well, and obtain a modified solution; S02: adding nanocellulose to a sufficient amount of modification liquid for ultrasonic modification treatment, and after the modification is completed, filtering and drying are performed to obtain modified nanocellulose.
[0029] The mass ratio of nano zinc oxide, hydroxyapatite and yttrium nitrate solution in this embodiment is 3:2:5, wherein the mass fraction of yttrium nitrate solution is 2%.
[0030] The ultrasonic modification treatment time of this embodiment is 35 minutes, and the ultrasonic power is 400 W; the nanocellulose is lignin nanocellulose.
[0031] The preparation method of the modified filler of this embodiment is: S01: Prepare a sodium silicate solution with a mass fraction of 4%, then add 1 part of stearic acid, 1 part of sodium dodecyl sulfate and 2 parts of nano-alumina agent to 5 parts of the sodium silicate solution with a mass fraction of 4% by weight, stir evenly, and obtain a modified sodium silicate solution; S02: Preheat nano titanium dioxide at 60°C for 1 hour to obtain preheated nano titanium dioxide; mix the preheated nano titanium dioxide and modified sodium silicate solution in a weight ratio of 2:5, and ball mill them at a ball milling speed of 1000r / min for 2 hours. After the ball milling is completed, filter and dry to obtain a modified filler.
[0032] The preparation method of the nano-alumina agent of this embodiment is as follows: nano-alumina, dopamine hydrochloride solution and lanthanum oxide are stirred in a weight ratio of 3:5:1, and after stirring, the stirring is completed, the nano-alumina agent is filtered and dried to obtain the nano-alumina agent; The mass fraction of dopamine hydrochloride solution is 3%; the stirring speed of the stirring treatment is 450 r / min, the stirring time is 1 hour, and the stirring temperature is 60°C.
[0033] A method for preparing a high light-transmittance PVC film of this embodiment comprises the following steps: The raw materials are weighed according to weight parts, and the raw materials are mixed uniformly to obtain a blend; the blend is melt-extruded in an extruder, and then blow-molded, extruded into a film through a herringbone plate and a traction guide roller, and finally cooled and rolled to obtain a high-light-transmittance PVC film.
[0034] The melt extrusion in the extruder of this embodiment adopts a twin-screw extruder, the temperature of the first section is 180°C, the temperature of the second section is 200°C, the temperature of the third section is 210°C, the screw speed is 50r / min, and the aspect ratio is 40:1.
[0035] Embodiment 2: A high light transmittance PVC film, comprising the following raw materials in parts by weight: 55 parts of PVC resin, 11 parts of modified nanocellulose, 8 parts of modified filler, 8 parts of silane coupling agent, 6 parts of epoxidized soybean oil, 3 parts of heat stabilizer, and 3 parts of lubricant.
[0036] The silane coupling agent of this embodiment is silane coupling agent KH560; the heat stabilizer is barium zinc heat stabilizer; and the lubricant is sodium stearate.
[0037] The preparation method of the modified nanocellulose of this embodiment is: S01: Preparation of modified solution: S011: immerse nano zinc oxide and hydroxyapatite in yttrium nitrate solution and stir evenly, then filter and dry, and then heat calcine at 185°C for 1 hour. After calcination, cool naturally to room temperature to obtain nano zinc oxide agent; S012: adding 8% of alginate to a 4% chitosan solution, and then adding 8% sodium citrate solution which is 3 times the total mass of the chitosan solution, and stirring evenly to obtain a modified sodium citrate solution; S013: Add 7 parts of nano zinc oxide agent and 3 parts of silane coupling agent KH550 to 8 parts of modified sodium citrate solution by weight, stir well, and obtain a modified solution; S02: adding nanocellulose to a sufficient amount of modification liquid for ultrasonic modification treatment, and after the modification is completed, filtering and drying are performed to obtain modified nanocellulose.
[0038] The mass ratio of nano zinc oxide, hydroxyapatite and yttrium nitrate solution in this embodiment is 4:2:7; wherein the mass fraction of yttrium nitrate solution is 5%.
[0039] The ultrasonic modification treatment time of this embodiment is 45 minutes, and the ultrasonic power is 450 W; the nanocellulose is lignin nanocellulose.
[0040] The preparation method of the modified filler of this embodiment is: S01: Prepare a sodium silicate solution with a mass fraction of 7%, then add 3 parts of stearic acid, 2 parts of sodium dodecyl sulfate and 3 parts of nano-alumina agent to 8 parts of the sodium silicate solution with a mass fraction of 7% by weight, stir evenly, and obtain a modified sodium silicate solution; S02: Preheat nano titanium dioxide at 60°C for 1 hour to obtain preheated nano titanium dioxide; mix the preheated nano titanium dioxide and modified sodium silicate solution in a weight ratio of 2:5, and ball mill them at a ball milling speed of 1000r / min for 2 hours. After the ball milling is completed, filter and dry to obtain a modified filler.
[0041] The preparation method of the nano-alumina agent of this embodiment is as follows: nano-alumina, dopamine hydrochloride solution and lanthanum oxide are stirred in a weight ratio of 3:7:1, and after stirring, the stirring is completed, the nano-alumina agent is filtered and dried to obtain the nano-alumina agent; The mass fraction of the dopamine hydrochloride solution is 36%; the stirring speed of the stirring treatment is 500 r / min, the stirring time is 1 hour, and the stirring temperature is 65°C.
[0042] A method for preparing a high light-transmittance PVC film of this embodiment comprises the following steps: The raw materials are weighed according to weight parts, and the raw materials are mixed uniformly to obtain a blend; the blend is melt-extruded in an extruder, and then blow-molded, extruded into a film through a herringbone plate and a traction guide roller, and finally cooled and rolled to obtain a high-light-transmittance PVC film.
[0043] The melt extrusion in the extruder of this embodiment adopts a twin-screw extruder, the temperature of the first section is 180°C, the temperature of the second section is 200°C, the temperature of the third section is 210°C, the screw speed is 50r / min, and the aspect ratio is 40:1.
[0044] Embodiment 3: A high light transmittance PVC film, comprising the following raw materials in parts by weight: 52.5 parts of PVC resin, 9 parts of modified nanocellulose, 7 parts of modified filler, 6.5 parts of silane coupling agent, 5 parts of epoxidized soybean oil, 2.5 parts of heat stabilizer, and 2.5 parts of lubricant.
[0045] The silane coupling agent of this embodiment is silane coupling agent KH560; the heat stabilizer is barium zinc heat stabilizer; and the lubricant is sodium stearate.
[0046] The preparation method of the modified nanocellulose of this embodiment is: S01: Preparation of modified solution: S011: immerse nano zinc oxide and hydroxyapatite in yttrium nitrate solution and stir evenly, then filter and dry, and then heat calcine at 180°C for 1 hour. After calcination, cool naturally to room temperature to obtain nano zinc oxide agent; S012: Add 6.5% of alginate to a 4% chitosan solution, and then add 8% sodium citrate solution which is 2.5 times the total mass of the chitosan solution, and stir evenly to obtain a modified sodium citrate solution; S013: Add 5.5 parts of nano zinc oxide agent and 2 parts of silane coupling agent KH550 to 6.5 parts of modified sodium citrate solution by weight, stir well, and obtain a modified solution; S02: adding nanocellulose to a sufficient amount of modification liquid for ultrasonic modification treatment, and after the modification is completed, filtering and drying are performed to obtain modified nanocellulose.
[0047] The mass ratio of nano zinc oxide, hydroxyapatite and yttrium nitrate solution in this embodiment is 3.5:2:6, wherein the mass fraction of yttrium nitrate solution is 3.5%.
[0048] The ultrasonic modification treatment time of this embodiment is 40 minutes, the ultrasonic power is 425W; the nanocellulose is lignin nanocellulose.
[0049] The preparation method of the modified filler of this embodiment is: S01: Prepare a sodium silicate solution with a mass fraction of 5.5%, then add 2 parts of stearic acid, 1.5 parts of sodium dodecyl sulfate and 2.5 parts of nano-alumina agent to 6.5 parts of the sodium silicate solution with a mass fraction of 5.5%, stir evenly, and obtain a modified sodium silicate solution; S02: Preheat nano titanium dioxide at 60°C for 1 hour to obtain preheated nano titanium dioxide; mix the preheated nano titanium dioxide and modified sodium silicate solution in a weight ratio of 2:5, and ball mill them at a ball milling speed of 1000r / min for 2 hours. After the ball milling is completed, filter and dry to obtain a modified filler.
[0050] The preparation method of the nano-alumina agent of this embodiment is as follows: nano-alumina, dopamine hydrochloride solution and lanthanum oxide are stirred in a weight ratio of 3:6:1, and after stirring, the stirring is completed, the nano-alumina agent is filtered and dried to obtain the nano-alumina agent; The mass fraction of dopamine hydrochloride solution is 4.5%; the stirring speed of the stirring treatment is 475 r / min, the stirring time is 1 hour, and the stirring temperature is 62.5°C.
[0051] A method for preparing a high light-transmittance PVC film of this embodiment comprises the following steps: The raw materials are weighed according to weight parts, and the raw materials are mixed uniformly to obtain a blend; the blend is melt-extruded in an extruder, and then blow-molded, extruded into a film through a herringbone plate and a traction guide roller, and finally cooled and rolled to obtain a high-light-transmittance PVC film.
[0052] The melt extrusion in the extruder of this embodiment adopts a twin-screw extruder, the temperature of the first section is 180°C, the temperature of the second section is 200°C, the temperature of the third section is 210°C, the screw speed is 50r / min, and the aspect ratio is 40:1.
[0053] Comparative Example 1: The difference from Example 3 is that no modified nanocellulose is added.
[0054] Comparative Example 2: The difference from Example 3 is that no modification liquid treatment is used in the preparation of modified nanocellulose.
[0055] Comparative Example 3: The difference from Example 3 is that no nano zinc oxide agent is added in the preparation of the modified solution.
[0056] Comparative Example 4: The difference from Example 3 is that the hydroxyapatite is not immersed in the yttrium nitrate solution for treatment in the preparation of the nano zinc oxide agent, and the nano zinc oxide agent is directly replaced by nano zinc oxide raw material.
[0057] Comparative Example 5: The difference from Example 3 is that the modified sodium citrate solution is replaced by a sodium citrate solution with a mass fraction of 8%.
[0058] Comparative Example 6: The difference from Example 3 is that no modified filler is added.
[0059] Comparative Example 7: The difference from Example 3 is that no preheated nano titanium dioxide is added to the modified filler.
[0060] Comparative Example 8: The difference from Example 3 is that no modified sodium silicate liquid is added to the modified filler.
[0061] Comparative Example 9: The difference from Example 3 is that stearic acid and sodium lauryl sulfate are not added to the modified sodium silicate solution.
[0062] Comparative Example 10: The difference from Example 3 is that the sodium silicate solution in the modified sodium silicate solution is directly replaced by water.
[0063] Comparative Example 11: The difference from Example 3 is that no nano alumina agent is added to the modified sodium silicate solution.
[0064] Comparative Example 12: The difference from Example 3 is that no nano alumina is added in the preparation of the nano alumina agent.
[0065] Comparative Example 13: The difference from Example 3 is that lanthanum oxide is not added in the preparation of the nano alumina agent.
[0066] Comparative Example 14: The difference from Example 3 is that water is used instead of dopamine hydrochloride solution in the preparation of nano-alumina agent.
[0067] Comparative Example 15: The difference from Example 3 is that the mass fraction of dopamine hydrochloride solution in the preparation of nano-alumina agent is 7%.
[0068] Conventional test: The light transmittance (tested according to GB / T2410-2008 standard) and mechanical properties of the products of Examples 1 to 3 and Comparative Examples 1 to 15 were tested. The test results are shown in Table 1.
[0069] Table 1 Performance test results of the products of Examples 1 to 3 and Comparative Examples 1 to 15 under normal conditions:
[0070] It can be seen from Comparative Examples 1 to 15 and Examples 1 to 3 that the product of Example 3 of the present invention has excellent light transmittance, transverse tensile strength and elongation at break, and the performance of the product can be improved in a coordinated manner; From Comparative Examples 1 to 15 and Example 3, it can be seen that when neither modified nanocellulose nor modified filler is added to the product, the performance of the product deteriorates significantly. When the two are coordinated and synergistic, the product performance effect is most obvious. The modified nanocellulose was not treated with a modification liquid, the modified liquid was not added with a nano zinc oxide agent, the nano zinc oxide agent was not treated by immersing hydroxyapatite in an yttrium nitrate solution, the nano zinc oxide agent was directly replaced by a nano zinc oxide raw material, and the modified sodium citrate solution was replaced by a sodium citrate solution with a mass fraction of 8%. The performance of the products showed a trend of deterioration. The modified nanocellulose improved by the modification liquid obtained by the specific method of the present invention had the most significant product performance effect. The performance of the products tended to deteriorate when preheated nano titanium dioxide was not added to the modified filler, and when modified sodium silicate solution was not added with stearic acid or sodium dodecyl sulfate, the sodium silicate solution was directly replaced with water, nano alumina was not added, nano alumina was not added in the preparation of the nano alumina, lanthanum oxide was not added in the preparation of the nano alumina, dopamine hydrochloride solution was replaced with water in the preparation of the nano alumina, and the mass fraction of dopamine hydrochloride solution in the preparation of the nano alumina was 7%. The performance of the products tended to deteriorate to varying degrees. The modified filler obtained by the nano-alumina agent obtained by the specific method of the present invention, combined with sodium silicate solution and specific stearic acid and sodium dodecyl sulfate, has the most obvious product performance effect. Other methods are not as significant as the present invention. The preparation of nano alumina is proprietary, and other raw materials are not as effective as the nano alumina of the present invention. At the same time, the mass fraction of dopamine hydrochloride solution is not within the range of the present invention, and there is a certain trend of deterioration. The specific mass fraction of dopamine hydrochloride solution also has a certain improvement trend on the performance of the present invention.
[0071] The present invention is further tested to test the stability of heat resistance and UV weather resistance.
[0072] The products of Examples 1 to 3 and Comparative Examples 1 to 15 were placed at 65°C for 5 hours and then irradiated with ultraviolet light for 1 hour at 300 kwh / m 2 Then place it at -5℃ for 5h. The above is one cycle. The cycle test is repeated 10 times to test the product's temperature resistance and UV weathering stability, that is, to test the product's light transmittance (tested in accordance with GB / T2410-2008 standard) and mechanical properties under high temperature, UV irradiation and low temperature conditions. The test results are shown in Table 2: Table 2 Performance test results of the products of Examples 1 to 3 and Comparative Examples 1 to 15 under high temperature, ultraviolet irradiation and low temperature conditions:
[0073] From Comparative Examples 1 to 15 and Example 3, it can be seen that when neither modified nanocellulose nor modified filler is added to the product, the performance of the product has a significant deterioration trend. Only when the raw materials of the present invention are blended and synergistically used, the performance stability of the product is the most excellent. At the same time, the performance of modified nanocellulose and modified fillers prepared by different methods tends to deteriorate. Only when the raw material formula and process of the present invention are used, the performance effect of the product is the most significant.
[0074] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0075] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high light transmittance PVC film, characterized in that: It includes the following raw materials in parts by weight: 50-55 parts of PVC resin, 7-11 parts of modified nanocellulose, 6-8 parts of modified filler, 5-8 parts of silane coupling agent, 4-6 parts of epoxidized soybean oil, 2-3 parts of heat stabilizer, 2-3 parts of lubricant; The preparation method of the modified nanocellulose is: S01: Preparation of modified solution: S011: immerse nano zinc oxide and hydroxyapatite in yttrium nitrate solution and stir evenly, then filter and dry, and then heat calcine at 175-185°C for 1 hour. After calcination, cool naturally to room temperature to obtain nano zinc oxide agent; S012: Add 5-8% of alginate to a 4% chitosan solution, and then add 8% sodium citrate solution which is 2-3 times the total mass of the chitosan solution, and stir evenly to obtain a modified sodium citrate solution; S013: Add 4 to 7 parts of nano zinc oxide and 1 to 3 parts of silane coupling agent KH550 to 5 to 8 parts of modified sodium citrate solution by weight, stir well, and obtain a modified solution; S02: adding nanocellulose to a sufficient amount of modification liquid for ultrasonic modification, filtering and drying after modification to obtain modified nanocellulose; The preparation method of the modified filler is: S01: Prepare a sodium silicate solution with a mass fraction of 4-7%, then add 1-3 parts of stearic acid, 1-2 parts of sodium dodecyl sulfate and 2-3 parts of nano-alumina agent to 5-8 parts of the sodium silicate solution with a mass fraction of 4-7%, and stir evenly to obtain a modified sodium silicate solution; S02: Preheat nano titanium dioxide at 60°C for 1 hour to obtain preheated nano titanium dioxide; mix the preheated nano titanium dioxide and modified sodium silicate solution in a weight ratio of 2:5, and ball mill them at a ball milling speed of 1000r / min for 2 hours. After the ball milling is completed, filter and dry to obtain a modified filler.
2. A high light transmittance PVC film according to claim 1, characterized in that: It includes the following raw materials in parts by weight: 52.5 parts of PVC resin, 9 parts of modified nanocellulose, 7 parts of modified filler, 6.5 parts of silane coupling agent, 5 parts of epoxidized soybean oil, 2.5 parts of heat stabilizer, and 2.5 parts of lubricant.
3. A high light transmittance PVC film according to claim 1, characterized in that: The silane coupling agent is silane coupling agent KH560; the heat stabilizer is barium zinc heat stabilizer; and the lubricant is sodium stearate.
4. The high light transmittance PVC film according to claim 1, characterized in that: The mass ratio of the nano zinc oxide, hydroxyapatite and yttrium nitrate solution is (3-4):2:(5-7); The mass fraction of yttrium nitrate solution is 2~5%.
5. The high light transmittance PVC film according to claim 1, characterized in that: The ultrasonic modification treatment time is 35-45 minutes, and the ultrasonic power is 400-450W.
6. The high light transmittance PVC film according to claim 1, characterized in that: The nanocellulose is lignin nanocellulose.
7. The high light transmittance PVC film according to claim 1, characterized in that: The preparation method of the nano alumina agent comprises: stirring the nano alumina, dopamine hydrochloride solution and lanthanum oxide according to a weight ratio of 3: (5-7): 1, filtering and drying after the stirring is completed, so as to obtain the nano alumina agent.
8. The high light transmittance PVC film according to claim 7, characterized in that: The mass fraction of the dopamine hydrochloride solution is 3-6%; the stirring speed of the stirring treatment is 450-500 r / min, the stirring time is 1 hour, and the stirring temperature is 60-65° C.
9. A method for preparing a high light transmittance PVC film, for preparing a high light transmittance PVC film as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: The raw materials are weighed according to weight parts, and the raw materials are mixed uniformly to obtain a blend; the blend is melted and extruded in an extruder, and then blown, extruded into a film through a herringbone plate and a traction guide roller, and finally cooled and rolled to obtain a high-light-transmittance PVC film.
10. The method for preparing a high light transmittance PVC film according to claim 9, characterized in that: The melt extrusion in the extruder adopts a twin-screw extruder, the temperature of the first section is 180°C, the temperature of the second section is 200°C, the temperature of the third section is 210°C, the screw speed is 50r / min, and the aspect ratio is 40:1.
Citation Information
Patent Citations
Transparent composite PVC electric wire
CN111073182A
High-strength high-whiteness transparent glaze, ceramic and preparation method of high-strength high-whiteness transparent glaze
CN119241074A
Transparent vinyl chloride resin composition and molded product
JP2008001840A
Modified cellulose fiber
JP2018199755A
Modified cellulose nanofiber and resin composition containing modified cellulose nanofiber
JP2021059723A